Rosella Flower Extract Prevent Increasing of Interleukin-6 and Amyloid-β Levels in Brain Tissue of Heated Diet-Treated Rats - Ratna, Ardhiyanti Puspita; Soeharto, Setyawati; widjajanto, Edi; Falyani, Silvy Amalia; Batmomolin, Pia Bataif (Graduate School, Universitas Brawijaya, 2018)
Heated food is a source of formation of various types of Advanced Glycation Endproducts (AGEs). One of which is N-carboxymethyl-lysine (CML) that is often used as a sign of the formation of AGEs in the diet. The accumulation of AGEs in the brain can trigger neurodegenerative conditions. It also accelerates the accumulation of Amyloid β and proinflammatory cytokines which exacerbate neurodegeneration. Hibiscus sabdariffa L or rosella known to have antiglycation, antioxidant, and anti-inflammatory effects. This study aims to prove the effect of food heating to the increasing levels of CML serum and evaluate the effects of daily intake of Rosella extract IL-6 levels and Amyloid β in the Wistar rats' brain given a diet high of AGEs. This experimental study with post test only control group design was conducted using 25 white male rats Wistar strain (Rattus novergicus) which were divided into 5 groups namely positive control, negative control, the treatment group with rosella dose 200mg.kgBW-1, 300mg.kgBW-1, and 400mg.kgBW-1. The high diets of AGEs are given for 12 weeks, and it was added to the rosella extract with various doses on the 9th to 12th weeks. The examination of CML serum level, interleukin 6 brain level, and Amyloid β of the brain was carried by ELISA. This study found differences between CML serum level of rats which fed a standard diet and the one that was given a heated diet (p= 0.0001). It also found that rosella flower extract can prevent the increasing levels of interleukin 6 and Amyloid β in the brain tissue of rats which were given a heated diet, and both effective doses were on 200mg.kgBW-1. Keywords: Advanced Glycation End products, Amyloid β, Interleukin 6, N-carboxymethyl-lysine, Rosella.